«Fugit irreparabile tempus» en La Retraite y Le lac de Lamartine y en las Rimas IV, LIII, LIV, LVI de Bécquer - Lorente Carrillo, Yolanda; Martínez Cuadrado, Jerónimo (Estudios Románicos, 2009)
This article was born from an atempt to demonstrate that, in spite of the prior and obvious differences we know, the concern about the inexorable passage of time is latent in the work of both poets, Lamartine et Bécquer, a French and a Spanish poet from nineteenth-century Romanticism. This concern appears in several of their poems, wich respectively belong to the works Les Méditations and Las Rimas, even though they develop entirely different formal structures.